Cost structures in defined contribution systems: The case of Singapore's Central Provident Fund - KOH, Benedict S. K. (Institutional Knowledge at Singapore Management University, 2008)
Retirement systems are increasingly asked to do an ever-better job of enhancing the performance of pension investments. The Singaporean Central Provident Fund permits pension system participants to keep their money in a government-run investment pool, or if they wish, they may select professionally managed unit trusts for their retirement accumulations. Opting for investment choice also exposes members to additional investment costs not charged by the government-managed account. This paper explores the charges levied by the private fund managers and we show that foreign ownership, active style of management and equity/balanced funds tend to be most expensive. We conclude with a discussion of policy options available to reduce retirement system costs.